Radial positive solutions for Neumann problems without growth restrictions. Issue 6 (3rd June 2017) - Ma, Ruyun; Gao, Hongliang; Chen, Tianlan
Abstract: We study the existence of positive increasing radial solutions for Neumann problems in the unit ball We do not impose any growth condition on the nonlinearity at infinity. Our result is optimal and extends one of the main results in Bonheure et al. [Ann. Inst. H. Poincaré Anal. Non Linéaire. 2012;29:573–588]. The proof of our main result is based upon bifurcation techniques.